Penggunaan Teknik Konseling Diadik Dalam Mengidentifikasi Bentuk Perilaku Bullying Siswa Kelas XI IPA 1 Madrasah Aliyah Negeri 2 Halmahera Utara - Nurmutmainnah M. Ahmad; Nurda Rasid (Universitas Khairun, 2023)
This study aims to identify forms of bullying behavior in class XI IPA 1 Madrasah Aliyah Negeri 2 Halmahera Utara by using dyadic counseling techniques. This research was conducted using classroom action research methods (classroom action research). Collecting data using interview and observation techniques. The research subjects amounted to one person. The data obtained is described in the form of open coding and student observation tables. The results of the study show that students begin to understand that bullying behavior is a negative action and students think about what to do first so they won't hurt or bully their friends. And dyadic counseling techniques have proven to be more effective in increasing student awareness and knowledge in an effort to overcome bullying at MAN 2 North Halmahera.